(untitled) (Wilmington, Del., 1994)
This book presents readers with scholarship on public celebrations and popular culture throughout Mexican history. Leading scholars from the Americas and Great Britain discuss aspects of Mexico's popular culture from the seventeenth century to the present. The vast range of Mexican expression is examined, including Corpus Christi celebrations, New Spain, stone murals, and folk theater. Filling a need that becomes ever more pressing, this volume provides fresh insights
Keywords: Festivals,Lễ hội,Rites and ceremonies,Mexico,Mexico,Nghi lễ và lễ nghi; Social life and customs,Đời sống xã hội và phong tục; Mexico,Mexico,Mexico,Mexico